Design and Validation of an Intelligent Assistance and Monitoring System for the Safety of Vulnerable People - Flores Mozombite, Carolina Izanie; Carranza Escobedo, Pedro; Bravo Huivin, Elizabeth Kristina; Boñon Silva, Cesia Elizabeth; Veneros Castro, Candy Vanesa (LACCEI, 2025)
This study addresses the conceptual design and projective validation of an intelligent assistance and monitoring system aimed at vulnerable people in Trujillo, Peru. This project is aimed at improving safety and emergency response for older adults, at-risk women, and people with disabilities. We worked with a representative sample of 367 people, selected from a base population of 18,600 older adults, applying surveys and functional simulations, and with the support of specialists in health and citizen safety. The results demonstrate a high acceptance and viability of the technological solution, as well as its potential to strengthen the autonomy and protection of users in urban environments. The study lays the groundwork for future real implementations and the development of accessible assistive technologies in the Peruvian context.